Secondary hyperperfusion injury following surgical evacuation for acute isolated epidural hematoma with concurrent cerebral herniation - Huang, Wei; Li, Jun; Wang, Wen-hao; Zhang, Yuan; Luo, Fei; Hu, Lian-Shui; Lin, Jun-Ming (Frontiers in Neurology, 2023)
Objective Hemispherical cerebral swelling or even encephalocele after head trauma is a common complication and has been well elucidated previously. However, few studies have focused on the secondary brain hemorrhage or edema occurring regionally but not hemispherically in the cerebral parenchyma just underneath the surgically evacuated hematoma during or at a very early stage post-surgery. Methods In order to explore the characteristics, hemodynamic mechanisms, and optimized treatment of a novel peri-operative complication in patients with isolated acute epidural hematoma (EDH), clinical data of 157 patients with acute-isolated EDH who underwent surgical intervention were reviewed retrospectively. Risk factors including demographic characteristics, admission Glasgow Coma Score, preoperative hemorrhagic shock, anatomical location, and morphological parameters of epidural hematoma, as well as the extent and duration of cerebral herniation on physical examination and radiographic evaluation were considered. Results It suggested that secondary intracerebral hemorrhage or edema was determined in 12 of 157 patients within 6 h after surgical hematoma evacuation. It was featured by remarkable, regional hyperperfusion on the computed tomography (CT) perfusion images and associated with a relatively poor neurological prognosis. In addition to concurrent cerebral herniation, which was found to be a prerequisite for the development of this novel complication, multivariate logistic regression further showed four independent risk factors contributing to this type of secondary hyperperfusion injury: cerebral herniation that lasted longer than 2 h, hematomas that were located in the non-temporal region, hematomas that were thicker than 40 mm, and hematomas occurring in pediatric and elderly patients. Conclusion Secondary brain hemorrhage or edema occurring within an early perioperative period of hematoma-evacuation craniotomy for acute-isolated EDH is a rarely described hyperperfusion injury. Because it plays an important prognostic influence on patients’ neurological recovery, optimized treatment should be given to block or reduce the consequent secondary brain injuries.